2006
DOI: 10.1038/sj.ki.5001578
|View full text |Cite
|
Sign up to set email alerts
|

Combined AGE inhibition and ACEi decreases the progression of established diabetic nephropathy in B6 db/db mice

Abstract: The accumulation of advanced glycation end products (AGE) is a key factor in diabetic nephropathy (DN). Pyridoxamine inhibits AGE formation and protects against type I DN. Herein we tested: (1) whether C57BL6 db/db mice as a model of established type II DN resembled patients treated with drugs which inhibit angiotensin II action; (2) whether pyridoxamine was effective as a single therapy; and (3) whether pyridoxamine would add to the benefit of angiotensin-converting enzyme inhibition (ACEi) by enalapril. In f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 36 publications
1
51
1
1
Order By: Relevance
“…This agent is a derivative of vitamin B6 and can reduce serum AGE levels by blocking AGE formation with no effect on the blood levels of glucose or lipids 22.…”
Section: Methodsmentioning
confidence: 99%
“…This agent is a derivative of vitamin B6 and can reduce serum AGE levels by blocking AGE formation with no effect on the blood levels of glucose or lipids 22.…”
Section: Methodsmentioning
confidence: 99%
“…10,11 Pyridorin also inhibited formation of advanced glycation and lipoxidation end products and controlled plasma lipids, while limiting the loss of renal function and reducing albuminuria in Zucker rats. 12 Progression of diabetic glomerular histopathologic findings over 15 weeks of therapy decreased in db/db diabetic mice, 13 and improved albuminuria was reported in the KK-A y /Ta mouse model of diabetic nephropathy. 14 Despite the positive preclinical experience, we failed to show that Pyridorin altered the progressive loss of renal function anticipated in our patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Several preclinical studies in rat models of diabetic nephropathy have demonstrated oral Pyridorin to be efficacious in preserving renal function. [10][11][12][13][14] Two small, 24-week clinical safety trials have reported an apparent decrease in the rate of loss of renal function associated with Pyridorin treatment. 15 The purpose of our study was to determine whether 1 year of therapy with Pyridorin delayed the progressive loss of renal function in patients with type 2 diabetes mellitus and advanced nephropathy.…”
mentioning
confidence: 99%
“…2,3 Most experimental studies of RAS blockade have used chronic nephropathy models resulting from diabetes, 4,5 hypertension, 6,7 nephrotoxicity, 8 reduction of renal mass, 6,9 or chronic renal injury subsequent to acute mesangiolysis induced in rats by anti-Thy-1 antibody 10,11 or subsequent to establishment of an immune complex-induced glomerulonephritis. 12,13 Similarly, the efficacy of RAS blockade in human kidney diseases has been best demonstrated in patients with diabetic nephropathy, 14,15 hypertension, 16,17 or chronic kidney disease (CKD) arising from multiple causes.…”
mentioning
confidence: 99%